Conservative versus Surgical Therapy in Managing Patients with Facial Nerve Palsy Due to the Temporal Bone Fracture. Issue 1 (March 2019) - Abbaszadeh-Kasbi, Ali; Kouhi, Ali; Ashtiani, Mohammad Taghi Khorsandi; Anari, MahtabRabbani; Yazdi, AlirezaKarimi; Emami, Hamed
Facial nerve paralysis is classified into immediate or delayed-onset palsy, and affected patients should be treated through conservative or surgical therapy. Appropriate treatment is somewhat debated as well as proper time for performing surgery. This study aimed to assess treatment outcome between conservatively and surgically treated groups and to determine the appropriate time of surgery in selected patients for surgery. Twenty-four patients from April 2008 to July 2015 were included. Performing decompression surgery within the first 2 months following the trauma accompanies a better prognosis ( p -value < 0.05). Eleven patients were managed conservatively, and 4 of them demonstrated immediate onset and 7 indicated delayed onset. Nine patients obtained normal nerve function, one patient had partial palsy, and one of them had complete palsy. There was no significant difference in the rate of recovery between types of the treatment ( p -value > 0.05). Decompression surgery is recommended in the first 2 months after the trauma for immediate onset and also complete degeneration on electroneuronography.